2016
DOI: 10.1287/mnsc.2015.2315
|View full text |Cite
|
Sign up to set email alerts
|

Bending the Pipeline? Executive Search and Gender Inequality in Hiring for Top Management Jobs

Abstract: We study the sources of women's underrepresentation in hiring for top management jobs, by focusing on the context of executive search. Using data that include proprietary information on 10,970 individuals considered by a search firm, we examine the sources of the low proportion of women placed in senior roles. Contrary to received wisdom, we find limited evidence that demand-side screeners strongly contribute to gender disadvantage in this setting. What gender differences exist tend to play out at the start of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(78 citation statements)
references
References 101 publications
1
76
0
1
Order By: Relevance
“…8 Identifying the proportion of women who are qualified for senior leadership positions is, of course, difficult. However, see Fernandez-Mateo and Fernandez (2016) for recent advancements on this front. See also Hwang et al (2019), who find that markets anticipate a supply-side constraint for firms in California following the imposition of a board quota.…”
Section: Endnotesmentioning
confidence: 99%
“…8 Identifying the proportion of women who are qualified for senior leadership positions is, of course, difficult. However, see Fernandez-Mateo and Fernandez (2016) for recent advancements on this front. See also Hwang et al (2019), who find that markets anticipate a supply-side constraint for firms in California following the imposition of a board quota.…”
Section: Endnotesmentioning
confidence: 99%
“…Statistical analyses of observational data from employers operating in male-dominated fieldsincluding an executive search firm (Fernandez-Mateo and Fernandez 2016), a high technology company (Petersen, Saporta and Seidel 2000) and BioPharma firm (Fernandez and Abraham 2011) -all found that, when the gender composition of the applicant pool is accounted for, men and women were equally likely to be hired. Similar patterns were evident in analyses of hiring data from organizations in female-dominated fields, including a large public service organization (Petersen, Saporta and Seidel 2005) and a retail bank's customer service division (Fernandez, Castilla and Moore 2000).…”
Section: Do Employer Hiring Decisions Reproduce Sex Segregation?mentioning
confidence: 99%
“…The larger amount of information involved in evaluating the quality of a pool -theoretically, all the available pertinent information on all the applicants in the pool -increases search costs and the likelihood employers will rely on visible social characteristics. Indeed, previous research suggests that women are more likely to be disadvantaged by decisions made during hiring stages with higher search costs, such as when employers construct long lists from applicant pools, but are less so during those with lower search costs, such as when employers decide whom to offer employment from among those interviewed (Fernandez-Mateo and Fernandez 2016;Fernandez-Mateo and King 2011;Fernandez and Mors 2008).…”
Section: From Whom To Hire To Whether To Hirementioning
confidence: 99%
See 1 more Smart Citation
“…In attempting to explain the gender gap in science, and professional labor markets more broadly, much research has focused on the "glass ceiling" -the idea that women hit invisible barriers beyond which they cannot advance when reaching the upper echelons of their organizations or institutional environments (Rosser, 2004). Because this literature focuses on characterizing barriers these "survivors" still face when having climbed near the top of the career ladder (e.g., Hoisl and Mariani, 2016), and perhaps partly because of richer data availability on the trajectory of senior women, recent research has called attention to the fact that we know relatively little about roadblocks women may face much earlier in their careers, both in science (Lerchenmueller and Sorenson, 2018) and in the broader labor market (Fernandez-Mateo and Fernandez, 2016).…”
Section: Introductionmentioning
confidence: 99%